2021
DOI: 10.1007/s10198-021-01407-9
|View full text |Cite
|
Sign up to set email alerts
|

Willingness-to-pay for cancer treatment and outcome: a systematic review

Abstract: Background Understanding patient preferences in cancer management is essential for shared decision-making. Patient or societal willingness-to-pay (WTP) for desired outcomes in cancer management represents their preferences and values of these outcomes. Objective The aim of this systematic review is to critically evaluate how current literature has addressed WTP in relation to cancer treatment and achievement of outcomes. Methods Seven databases were searched from inception until 2 March 2021 to include studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…In a similar study conducted among Malaysian population, the estimated value for the costeffectiveness threshold was $9,000 [23]. Furthermore, a meta-analysis of 54 studies evaluating WTP for cancer treatment and outcomes indicated that QALY exhibits the highest WTP ($11,498-$ 589,822) compared to 1-year survival, quality of life improvement, and pain reduction [24].…”
Section: Discussionmentioning
confidence: 93%
“…In a similar study conducted among Malaysian population, the estimated value for the costeffectiveness threshold was $9,000 [23]. Furthermore, a meta-analysis of 54 studies evaluating WTP for cancer treatment and outcomes indicated that QALY exhibits the highest WTP ($11,498-$ 589,822) compared to 1-year survival, quality of life improvement, and pain reduction [24].…”
Section: Discussionmentioning
confidence: 93%
“…The per-capita GDP and WTP thresholds vary widely worldwide [ 22 , 23 ]. Our results suggest that adjunct capecitabine maintenance therapy could be treated as cost-effective when the per-capita GDP is above $876.7 (i.e., one-third of ICER), while only 24 out of 190 countries/regions (12.6%) are with per-capita GDP less than $876.7 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 This is an important area of research, especially in interventions for cancer patients, where there are uncertainties about WTP limits. [57][58][59][60] Future studies could provide valuable insight by weighing patient & stakeholder preferences for cost-utility of germline testing compared to other health care needs.…”
Section: Discussionmentioning
confidence: 99%